On persistence of a Nicholson-type system with multiple delays and nonlinear harvesting - Amster, Pablo; Bondorevsky, Melanie (Nonlinear analysis: real world applications, 2022)
An N-dimensional generalization of Nicholson’s equation is analyzed. We consider a model including multiple delays, nonlinear coefficients and a nonlinear harvesting term. Inspired by previous results in this subject, we obtain sufficient conditions to guarantee strong and uniform persistence. Furthermore, under extra suitable hypotheses we prove the existence of T-periodic solutions and, reversing the prior conditions in a convenient manner, we show that the zero is a global attractor.